Earnings gap, cohort effect and economic assimilation of immigrants from mainland China, Hong Kong and Taiwan in the United States - Carl Lin (Institute for the Study of Labor (IZA), 2013)
Using 1990, 2000 censuses and a 2010 survey, I examine the economic performance of ethnically Chinese immigrants from mainland China, Hong Kong and Taiwan (CHT) in the U.S. labor market. Since 1990, relative wages of CHT migrants have been escalating in contrast to other immigrants. I show these widening gaps are largely explained by individual's endowments, mostly education. Rising U.S.-earned degrees by CHT migrants can account for this relatively successful economic assimilation. Cohort analysis shows that the economic performance of CHT migrants admitted to the U.S. has been improving, even allowing for the effect of aging.
Keywords: J31; J61; J24; 330; Chinese immigration; economic assimilation; Oaxaca decomposition; synthetic cohort analysis